2012
DOI: 10.1186/1423-0127-19-63
|View full text |Cite
|
Sign up to set email alerts
|

The paracrine effect of exogenous growth hormone alleviates dysmorphogenesis caused by tbx5 deficiency in zebrafish (Danio rerio) embryos

Abstract: BackgroundDysmorphogenesis and multiple organ defects are well known in zebrafish (Danio rerio) embryos with T-box transcription factor 5 (tbx5) deficiencies, mimicking human Holt-Oram syndrome.MethodsUsing an oligonucleotide-based microarray analysis to study the expression of special genes in tbx5 morphants, we demonstrated that GH and some GH-related genes were markedly downregulated. Zebrafish embryos microinjected with tbx5-morpholino (MO) antisense RNA and mismatched antisense RNA in the 1-cell stage ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This study showed that exogenous IGF-I induced positive effects on embryogenesis in wild-type zebrafish embryos (Fig. 3C and I ), whereas a previous study reported that exogenous GH had little effect [ 21 ]. Additionally, it has been reported that the embryogenic effect of GH probably occurs via an IGF-I-independent mechanism [ 25 ].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This study showed that exogenous IGF-I induced positive effects on embryogenesis in wild-type zebrafish embryos (Fig. 3C and I ), whereas a previous study reported that exogenous GH had little effect [ 21 ]. Additionally, it has been reported that the embryogenic effect of GH probably occurs via an IGF-I-independent mechanism [ 25 ].…”
Section: Discussionmentioning
confidence: 62%
“…tbx5 is a regulator of apoptosis and cell growth, and tbx5 deficiency can induce cell apoptosis and alter cell cycling [ 22 24 ]. Although the role of IGF-I is not well-characterized in zebrafish embryogenesis, previous studies have found that tbx5 morphants have down-regulated gh and GH-related genes, including igf1 [ 21 ]. In this study, we found that exogenous recombinant human IGF-I administration ameliorated dysmorphogenesis, increased akt2 and erk1 expression , normalized bcl2 and bad expression, suppressed cell apoptosis, and improved survival rates in tbx5 morphants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the Zebrafish AB strain carrying a specific transgene (Tg, cmlc2::EGFP; cmlc2:H2AFZmCherry) cy3 in this study. The details of the maintenance and breeding of zebrafish and embryo collection have been previously published [21,22,23].…”
Section: Methodsmentioning
confidence: 99%